Pilot investigation of the oxygen demands and metabolic cost of incremental shuttle walking and treadmill walking in patients with cardiovascular disease - Almodhy, M (BMJ Publishing Group, 2014)
OBJECTIVE: To determine if the metabolic cost of the incremental shuttle-walking test protocol is the same as treadmill walking or predicted values of walking-speed equations. SETTING: Primary care (community-based cardiac rehabilitation). PARTICIPANTS: Eight Caucasian cardiac rehabilitation patients (7 males) with a mean age of 67±5.2 years. PRIMARY AND SECONDARY OUTCOME MEASURES: Oxygen consumption, metabolic power and energy cost of walking during treadmill and shuttle walking performed in a balanced order with 1 week between trials. RESULTS: Average overall energy cost per metre was higher during treadmill walking (3.22±0.55 J kg/m) than during shuttle walking (3.00±0.41 J kg/m). There were significant post hoc effects at 0.67 m/s (p<0.004) and 0.84 m/s (p<0.001), where the energy cost of treadmill walking was significantly higher than that of shuttle walking. This pattern was reversed at walking speeds 1.52 m/s (p<0.042) and 1.69 m/s (p<0.007) where shuttle walking had a greater energy cost per metre than treadmill walking. At all walking speeds, the energy cost of shuttle walking was higher than that predicted using the American College of Sports Medicine walking equations. CONCLUSIONS: The energetic demands of shuttle walking were fundamentally different from those of treadmill walking and should not be directly compared. We warn against estimating the metabolic cost of the incremental shuttle-walking test using the current walking-speed equations.